The Medicine Tree: Unsettling palaeoecological perceptions of past environments and human activity. (October 2017) - Richer, Suzi; Gearey, Benjamin
In this paper, we consider palaeoecological approaches to past landscapes and reflect upon how these are relevant to archaeological themes concerning concepts of environmental change and the role of past and present human communities in these processes. In particular, we highlight the importance of local context in the perception and understanding of landscape. Utilising a case study from Nepal, we look to 'unsettle' a conventional palaeoecological interpretation of a pollen record, originally constructed on western ecological principles, and instead draw on an interpretative perspective rooted in local Buddhist ecological knowledge, or a 'folk taxonomy', known as 'The Medicine Tree'. We discuss how the interpretations of patterns and processes of vegetation change from a pollen record are not necessarily absolute. In particular, we outline how the palaeoecological frame of enquiry and reference is rooted in an essentially Eurocentric, Western scientific paradigm, which, in turn, shapes how we perceive and conceive of past landscapes and the role of 'anthropogenic impact' on vegetation. The aim of this is not to suggest that scientific approaches to the 'reconstruction' of past landscapes are necessarily invalid, but to illustrate how 'empirical' scientific methods and interpretations in archaeological science are contingent upon specific social and cultural frames of reference. We discuss the broader relevance of this, such as how we interpret past human activity and perception of landscape change, the ways in which we might look to mobilise research in the context of contemporary problems, issues concerning 'degraded landscapes' and how we incorporate local and archaeological perspectives with palaeoecology within an interconnected and iterative process.